The innocence game ebook - Harvey, Michael (2013)
A cold case is about to do supernova and three students will learn the price of innocence. At Northwestern's renowned journalism school, Ian Joyce has been invited to participate in a prestigious seminar that investigates wrongful convictions and forgotten cases. With only two other classmates—beautiful, strong-willed Sarah Gold and enigmatically brilliant Jake Havens—he begins to investigate the long-ago murder of a young boy, ten-year-old Skylar Wingate, last seen walking home from school, his body discovered three days later in a forest preserve. His alleged killer was murdered decades ago in jail. But two chilling clues delivered to Jake's house suggest that the killer is still very much alive, and, in fact, in their midst. As the evidence mounts, the three classmates find themselves drawn into web of distrust, deceit, and corruption that will lead from the grittiest corners of Chicago and to the shores of Lake Michigan.